Development of bio-green floating aquaculture system as bioremediation for improvement of water quality and growth performance of red hybrid tilapia - Sopawong, Arissara (2022)
Aquaculture has been recognised as an important sector for income generation and economic development for many countries, especially in Asia where 89% of aquaculture products are generated. While aquaculture is the fastest-growing food sector worldwide, its production is still limited by feed quality, water quality deterioration, and diseases. In addition, untreated waste discharges from aquaculture activities can cause eutrophication in public waters. This study aimed to reduce nutrients, improve water quality and increase fish production in aquaculture systems by enhancing the nutrient uptake rate using plants and biofilms assembled as an efficient nutrient uptake system known as a bio-green floating aquaculture system (BFAS). The bio-green floating aquaculture system (BFAS) comprised an assemblage of biofilm-coated substrates and plants which were able to reduce nutrients, especially inorganic nitrogen and phosphorus from the aquaculture system. In this study, three different plant species; water spinach (Ipomoea aquatica; WS), lemon basil (Ocimum × africanum; LB), and aromatic basil (Ocimum basilicum; AB), single and in combination (WS, LB, AB, WS+LB, WS+AB, LB+AB, WS+LB+AB) were tested to determine their nutrient uptake ability and plant growth performances. The highest (P < 0.05) nutrient uptake removal (39.08% of total nitrogen, 88.06% of total ammonia nitrogen, 72.61% of nitrite+nitrate nitrogen, 82.06% of total phosphorus, and 77.75% of soluble reactive phosphate) and plant growth performance was shown better in two combinations of water spinach and lemon basil (WS+LB). A total of five different substrates (bamboo; BO, lava rock; LR, polyvinyl chloride; PVC, bio-ball; BA, bio-ring; BR) were used to investigate their periphyton abundance. Periphyton colonisation on lava rock and bamboo showed the highest (P < 0.05) biomass (2.18 ± 0.09 mg cm-2 and 2.05 ± 0.11 mg cm-2, respectively) and periphyton abundance on the substrate amongst all the substrates used. A combination of individually selected plants (water spinach and lemon basil) and selected substrates (lava rock and bamboo) were tested to determine nutrient uptake efficiency and plant growth performance. It was found that nutrient removal efficiency in a single substrate (lava rock) combined with a single plant (water spinach) was significantly higher (P < 0.05) compared to other treatments with reduction of TAN (88%), NO2-N (67%) and PO4-P (30%). Water spinach yield showed the highest (P < 0.05) production compared to lemon basil. Results of this study showed that the combination of lava rock and water spinach efficiently controlled water quality with less accumulation of TAN, NO2-N and PO4-P. In addition, the attached biofilm, coupled with microbial nitrification (Nitrospira, Nitrosomonas, Prosthecobacter) and denitrification (Acidovorax, Bosea, Dechloromonas, Flavobacterium, Thermomonas, Thiobacillus), also played a significant role in the removal of nitrogen in the water spinach integrated with the lava rock system. The development of BFAS using the selected plant (water spinach) integrated with the selected substrate (lava rock) with zero water exchange was used to investigate the efficiency of water quality improvement and production of monosex red tilapia (Oreochromis sp.) in 1000 L tanks. The growth performances of fish in BFAS were significantly higher (P < 0.05) compared to other treatments with the survival rate of 92.31% and specific growth rate of 3.58. The mean of nutrient concentrations in BFAS treatment were significantly lower (P < 0.05) compared to other treatments with the concentration of 0.01 mg L-1 in NH3-N, 0.06 mg L-1 in NO2-N and 0.75 mg L-1 in PO4-P. Treatment with BFAS had the lowest FCR (1.16 ± 0.03) and also better fish health conditions compared to the treatments with non-BFAS with water exchange (1.50 ± 0.05) and without water exchange (2.15 ± 0.02). Furthermore, heavy metal concentrations in fish and plants of BFAS were safe for human consumption as the accumulation levels of the heavy metals were lower than the recommended safe limit. In addition, the most dominant bacteria in BFAS including Bacteroidota, Proteobacteria, and Nitrospirota were found, which are very important for nutrient cycling in the aquaculture system. This study illustrated that the newly developed BFAS containing substrates (lava rock) and plants (water spinach) could maintain the optimal water quality, providing better fish production, plant yields and lower production cost for tilapia aquaculture system.